Pemanfaatan Media Sosial dalam Mengampanyekan Keilmuan Bidang Keperawatan pada Masyarakat - Siti Hapsah Pahira; Agus Rohmat Hidayat; Hanipah Hanipah (Jurnal Forum Kesehatan : Media Publikasi Kesehatan Ilmiah, 2021)
Abstract – Social media is one thing that cannot be avoided in this day and age. Social media has many functions such as communication media, educational media, information sharing media, buying and selling media. One of the uses of social media can be done as a media promotion. In the health sector, especially nursing, social media can be used as a means of delivering information related to health and nursing content. The purpose of this study was to demonstrate the use of social media as a means of increasing public attention in the field of nursing. The method used is a qualitative method with an explanatory research approach. The data used consisted of primary data and secondary data, both of which were obtained from observations by researchers. The results of the study indicate that the use of social media as a means of promoting health content can be carried out by people who have ties to the nursing field, especially experts and professionals. Provision of content must be adapted to the characteristics of each social media and its users. Even though the potential for using social media to convey education in the field of nursing is considered quite large, there are still several obstacles that must be overcome by social media activists.